1991
DOI: 10.1073/pnas.88.9.3554
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic protein S100 beta stimulates glial cell proliferation.

Abstract: Nervous system development involves a coordinated series ofevents, induding regulation ofcell piferation and differentiation by specific extracellular factors. SlOO( is a neurotrophic protein that has been implicated in regulation of cellular proliferation, but direct evidence was lacking. In this report, nanomolar concentrations of S1001 are shown to stimulate proliferation of rat C6 glioma cells and primary astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(185 citation statements)
references
References 58 publications
4
172
0
8
Order By: Relevance
“…Several previous reports suggested that the S100B protein functions as a trophic factor (17)(18)(19). However, mice completely lacking S100B developed normally and there was no detectable abnormality in histological architecture of the mutant brain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several previous reports suggested that the S100B protein functions as a trophic factor (17)(18)(19). However, mice completely lacking S100B developed normally and there was no detectable abnormality in histological architecture of the mutant brain.…”
Section: Discussionmentioning
confidence: 92%
“…Mutant mice reached sexual maturity and both male and female mice were fertile. Despite several lines of evidences suggesting that S100B has trophic activity for glia and neurons (17)(18)(19), no anatomical abnormalities were observed in mutant brains (data not shown). We observed no abnormalities in their home cage behavior for up to 18 months of age.…”
Section: S100b-null Mice Developedmentioning
confidence: 88%
“…The present results suggest that S100A1, but not S100A4, produced by the tumour cells could stimulate muscle proliferation and there are several possible explanations for this effect. However, the previously reported extracellular activity of some S100 proteins, notably the neuronal S100B, which is neurotrophic for cultured glial cells and astrocytes (Selinfreund et al, 1991), raises the possibility that S100A1 might exert its effect extracellularly on host muscle cells in vivo.…”
Section: (T) Invading Muscle Cells (M) (C) Primary Tumour Of Rama 37mentioning
confidence: 87%
“…Moreover, the increased S100ß and FGF-2 in reactive satellite cells of axotomized DRG and lesioned sciatic nerve may also be associated with local neovascularization, gliogenesis and repair 34 as well as to paracrine neuronal trophism and plasticity in remaining DRG peripheral motor neurons.…”
Section: Discussionmentioning
confidence: 99%